PENGEMBANGAN MEDIA QUIET BOOK BERBASIS MULTIMODAL PADA MATA PELAJARAN IPAS MATERI KEBERAGAMAN BUDAYA UNTUK SISWA KELAS IV SEKOLAH DASAR - Siti Raihan; Nur Amalia, Maghfira; Syamsuddin, Afdhal Fatawuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is a Research and Development (R&D) study using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The purpose of this study is to develop a Multimodal-Based Quiet Book learning media as a learning resource for cultural diversity material in fourth-grade elementary school IPAS learning. The product developed is a multimodal-based Quiet Book media that has undergone validation stages by material experts and media experts and has been tested on users. The results of the material and media validation were categorized as feasible. The results of the one-to-one, small group, and large group trials showed that the media was considered highly feasible by students. In addition, the responses from teachers and students toward the use of the media were very positive. Based on these results, the multimodal-based Quiet Book media is considered suitable for use as a learning medium to help students understand the cultural diversity of Indonesia in fourth-grade elementary school.